Higher education decisions and macroeconomic conditions at age eighteen - Jennifer Graves; Zoë Kuehn (SERIEs - Journal of the Spanish Economic Association, 2022)
Using individual data from PIAAC and data on youth unemployment for 18 countries, we test how macroeconomic conditions experienced at age eighteen affect the following decisions in post-secondary and tertiary education: (i) enrollment (ii) dropping-out, (iii) type of degree completed, (iv) area of specialization, and (v) time-to-degree. We also analyze how the effects vary by gender and parental background. Our findings differ across geographies (Anglo-Saxon, Southern European, Western European, and Scandinavian countries), which shows that the impacts of macroeconomic conditions on higher education decisions depend on context, such as labor markets and education systems. By analyzing various components of higher education together, we are able to obtain a clearer picture of how during economic downturns potential mechanisms interact to determine higher education decisions.
Keywords: E32; I21; I26; 330; Higher education decisions; Macroeconomic conditions; PIAAC